2018
DOI: 10.1177/0033294118793985
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Workplace Bullying Behaviors and Job Satisfaction: Moderated Mediation Analysis With Coping Self-Efficacy and Exposure to Bullying

Abstract: Previous research explored workplace climate as a factor of workplace bullying and coping with workplace bullying, but these concepts were not closely related to workplace bullying behaviors (WBBs). To examine whether the perceived exposure to bullying mediates the relationship between the climate of accepting WBBs and job satisfaction under the condition of different levels of WBBs coping self-efficacy beliefs, we performed moderated mediation analysis. The Negative Acts Questionnaire - Revised was given to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Interestingly, a significant indirect effect of experience of workplace incivility via acceptability on OCB-O was observed, which is the opposite of our expectation. However, this finding could be also possible given the positive correlation between experience of workplace bullying and acceptance of workplace bullying that can negatively impact on organizational outcomes such as job satisfaction (Vukelic et al , 2019). That is, if employees understand that their organizational culture is such that workplace incivility is common, accepted and tolerated, it may be true that their OCB toward the organization would be less likely in daily work-life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a significant indirect effect of experience of workplace incivility via acceptability on OCB-O was observed, which is the opposite of our expectation. However, this finding could be also possible given the positive correlation between experience of workplace bullying and acceptance of workplace bullying that can negatively impact on organizational outcomes such as job satisfaction (Vukelic et al , 2019). That is, if employees understand that their organizational culture is such that workplace incivility is common, accepted and tolerated, it may be true that their OCB toward the organization would be less likely in daily work-life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Moon and S anchez-Rodríguez (2021) compared acceptability of uncivil workplace behaviors among South Korean and Spanish employees and concluded that the former reported higher social and personal acceptability. Similarly, Vukelic et al (2019) examined the role of acceptability of bullying behaviors (e.g. ignoring, gossiping) in the workplace.…”
Section: Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace bullying is a common negative event like workplace exclusion (Stagg et al , 2011) and has a significantly negative impact on the sleep quality as well as mental health of employees (Magee et al , 2015). Therefore, many scholars call for attention to workplace bullying, especially how should individuals deal with workplace bullying (Escartin et al , 2011; Vukelic et al , 2019). Following the research of Zhao et al (2016), we speculate that workplace bullying, as a negative event, will also have an impact on employees’ knowledge hiding behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…First, the WPV-PMTP has an effect on the improvement of occupational coping self-efficacy. Indeed, studies have found support for the notion that the impact of job-related psychological distress may be associated with low coping self-efficacy [ 43 , 47 , 68 ]. Nurses’ perceived occupational coping self-efficacy may not only be a capacity, but also a specific functioning.…”
Section: Discussionmentioning
confidence: 99%